New species and new records in the genus Conocybe (Bolbitaceae) from China - Liu, Jing; Bau, Tolgor (Phytotaxa, 2018)
Two new species of Conocybe cylindrospora sp. nov., C. serrata sp. nov. are described herein with details illustration and morpho taxonomic features. In addition, two species like Conocybe fuscimarginata (Murrill) Singer and Pholiotina vexans (P.D. Orton) Bon are also reported for the first time from China. Molecular phylogenetic studies based on nrITS data help to distinguish the newly described species from all of its relatives. Conocybe cylindropora is characterized by its conical, hygrophanous pileus coloured orange, cylindrical to ellipsoid-oblong basidiospores, presence of lecithyform caulocystidia with a 2–4 μm long neck and a small glabrous head. Conocybe serrata is characterized by dentate veil on the pileus and basidiospores without germ pore.